2006
DOI: 10.1124/jpet.106.104620
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Stabilizer Ketotifen [4-(1-Methyl-4-piperidylidene)-4H-benzo[4,5]cyclohepta[1,2-b]thiophen-10(9H)-one Fumarate] Prevents Mucosal Mast Cell Hyperplasia and Intestinal Dysmotility in Experimental Trichinella spiralis Inflammation in the Rat

Abstract: Trichinella spiralis infection in rats induces hypermotility and an abnormal response to cholecystokinin (CCK) similar to motor disturbances observed in irritable bowel syndrome. Mast cell hyperplasia is also characteristic of this experimental model. The aim of our study was to correlate mast cell activity with the development of dysmotility and to demonstrate whether the mast cell stabilizer ketotifen [4-(1-methyl-4-piperidylidene)-4H-benzo [4,5]could prevent the development of intestine hypermotility. Sprag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 49 publications
6
48
0
1
Order By: Relevance
“…Ketotifen solutions were freshly prepared every 2 days. Similar treatment protocols have been used before, both clinically and preclinically, showing effects consistent with a ketotifen-mediated modulation of MC degranulation (14,19,35,42,45) …”
Section: Ketotifen Treatmentmentioning
confidence: 91%
See 3 more Smart Citations
“…Ketotifen solutions were freshly prepared every 2 days. Similar treatment protocols have been used before, both clinically and preclinically, showing effects consistent with a ketotifen-mediated modulation of MC degranulation (14,19,35,42,45) …”
Section: Ketotifen Treatmentmentioning
confidence: 91%
“…In that respect, one of the main features of T. spiralis infection is a persistent MC infiltration, an important source of endogenous proteinases (10,28,35). In particular, MC-derived tryptase has been suggested as one of the main endogenous activators of PAR-2 (1).…”
Section: G397mentioning
confidence: 99%
See 2 more Smart Citations
“…In the rat, on day 8 post infection (PI) with Nippostrongylus brasiliensis intestinal transit increases whereas on days 10, 12 and 14 no significant changes in relation to healthy animals are observed (Farmer, 1981). In Trichinella spiralis parasitized hosts, stimulation of mucosal mast cells to prolif-erate and release histamine causes local intestinal inflammation (Frieling et al, 1994) and hypermotility (Serna et al, 2006), symptoms which resemble those observed during irritable bowel syndrome. Notably, intense, long term infection of farm animals with trichinellosis (mainly in pigs, cattle and horses) frequently causes weight loss due to reduced productivity, high morbidity and also disqualifies meat intended for human consumption (Eckert, 1996).…”
mentioning
confidence: 99%